Нормативно-правовий захист комерційної таємниці в Україні - Горецький, О. В.; Олейнікова, О. І. (ХНУРЕ, 2022)
Тhe need for legal protection of trade secrets is due to the needs of the market economy and ensuring a competitive environment in business. The right to trade secrets is based on the de facto monopoly of the owner of the information, not on the legal monopoly on its use.